The type of contractual certificate and contractor’s compliance for construction project in Putrajaya / Nur Filzah Safra A’Kashah - A’Kashah, Nur Filzah Safra (2015)
The type of contractual certificate and requirement that needed to be fulfilled prior to issuance to contractor in Putrajaya is the topic for this practical report. The purpose of this report is for final submitted after practical training in last semester in Diploma Building Survey. There are two type of method currently in this practical report. Firstly, find the type of certificate that is use for the construction in Putrajaya. The type of certificate such as Certificate of Non-Completion (CNC), Certificate of Practical Completion (CPC), Handover Certificate (HOC), Certificate of Making Good Defect (CMGD) and Final Certificate (FC). Secondly, find the requirement that need to fulfil by contractor before getting the certificate. The contractor need to follow what is the Standard Form of Condition of Contract used before the certificate is released by Project Management Team (PMT).